Positive Youth Development in War-Affected Children in Uganda - Jody, L. McBrien; Jan, Stewart; Akullu, Betty Ezati (African Journals Online (AJOL), 2016)
The war in northern Uganda with Joseph Kony and his Lord’s Resistance Army (LRA) created over 20 years of terror and turmoil. Tens of thousands of youth were either abducted as child soldiers and/or sex slaves; or they were placed in internally displaced peoples’ (IDP) camps, where they lived with inadequate social provisions, such as food, health care, education, and safety. Our study used interviews and focus groups to learn about how these youth were coping post-war. In particular, we focused on youth with positive purpose and goals to understand ways in which they were supported to hold fast to positive development and life goals. Findings indicated that rehabilitation, financial support for education, role models, and sports/arts have helped many youth who experienced war in northern Uganda find pro-social purposes in their lives.